Basic Research OECD Framework Untuk Menanggulangi Base Erosion Profit Shifting : (Studi Komparasi Indonesia Malaysia) - Saparilla Worokinasih; Kartika Putri Kumalasari; Nurlita Sukma Alfandia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research is motivated by globalization and increasing digital economic activities, which by said activity Base Erosion and Profit Shifting (BEPS) is more likely to occur. With the issuance of a global consensus as a new framework, hopefully it can be a viable solution to digital economy taxation and reducing the amount of erosion of the tax base of each jurisdiction. The focus of this study was to find out the perspective of the two countries in implementing the two pillars of the global consensus. This research was conducted in 2021, after the Global Consensus Blueprint on Pillar I and II were issued by the OECD earlier in July. This research focused on providing an understanding about the global consensus regarding the two pillars. The approach used in this study was a qualitative approach. Data collection was carried out through literature studies and interviews from three representative parties, namely the governments, the academics, and the consultants. With the new taxation nexus, as well as profit allocation, and including the minimum tax rate which are the main points in both of the pillars, this research would cover the advantages and disadvantages for Indonesia in implementing the two pillars. In addition, it would also cover the arising challenges that the Indonesian government has to face; both in terms of legal and administrative perspective in the implementation of this new framework.